Oliver and the seawigs - Reeve, Philip; McIntyre, Sarah (New York : Random House, 2014)
"When Oliver's explorer parents go missing, he sets sail on the rescue mission with some new, unexpected friends"--Provided by publisher.
Map on endpapers.
Kirkus Review
Kirkus Review, April 2014
3-6
English.
Keywords: Explorers -- Juvenile fiction; Islands -- Juvenile fiction; Mermaids -- Juvenile fiction; Missing persons -- Juvenile fiction; Adventure and adventurers -- Fiction; Explorers -- Fiction; Humorous stories; Islands -- Fiction; Mermaids -- Fiction; Missing persons -- Fiction; Adventure fiction; Explorers -- Fiction; Humorous fiction; Islands -- Fiction; Mermaids and mermen -- Fiction; Missing persons -- Fiction